PENDIDIKAN MORAL ANAK USIA DINI MELALUI PENDEKATAN KONSTRUKTIVIS - Intan Kusumawati; Darmiyati Zuchdi (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Early childhood moral education through constructivist approaches focuses on implementing daily practices that are appropriate to the development of children from birth. Through a constructivist approach, the purpose of this study is to find out the development of children in all areas of the curriculum and all domains of development, both physical and moral. The goal of early childhood moral education is through a constructivist approach so that later children become independent students. In learning using a constructivist approach gives children the opportunity to learn about moral issues and behavior in real experience. Children build moral understanding through the social interactions they experience. Constructivist teachers facilitate children in the classroom so students can be directly involved in resolving conflicts or problems experienced by students in class, making decisions and social issues. The constructivist teacher builds children's interests and goals in building children's reasoning, children's experiments and encouraging children to be able to cooperate among all class members. The results of this study that the constructivist approach taken in the classroom makes children able to be autonomous and can make decisions, children can play games in groups through cooperation, and can conduct discussions or social and moral deliberations.